(untitled) (Journal of Advanced Veterinary and Animal Research, 2023)
Objective: Various disease complications are a risk of overweight or obesity, so losing weight can reduce the risk of diseases caused by obesity. Binahong leaf ethanol extract (Anredera cordifolia) is a weight-loss herbal preparation. Aim: This study aims to analyze whether A. cordifolia extract is effective in losing weight by affecting the mechanism of adipogenesis in an animal obesity model. Materials and Methods: Animals were grouped into six groups as follows: the normal diet (K1), the negative control group (K2), the positive control group with Orlistat at a dose of 20 mg/kg BW (K3), an ethanol extract of A. cordifolia leaves at doses of 50 mg/kg BW (P1), 100 mg/kg BW group (P2), and 150 mg/kg BW (P3). All rats were fed a diet that consisted of high fat for eight weeks, except K1. Afterward, the treatments were given based on group distribution. Then, the rats were treated based on their groups for 4 weeks, and the high-fat diet was still given during the treatment for the control groups (K2). Anthropometric examinations such as body weight, length, and the circumference of the abdomen were measured. Metabolic parameters, including blood glucose, cholesterol levels, triglyceride levels, and abdominal fat weight, were measured using molecular parameters that measured PI3K levels and Extracellular signal-regulated kinase (ERK) in abdominal fat tissue samples using the ELISA method. Results: ERK levels of abdominal fat were lowered in the treatment group using the extract of A. cordifolia (50 mg/kg BW (P1) and 100 mg/kg BW (P2)) compared to the control group that was given a high-fat diet without treatment. The control group, which was fed a high-fat diet without treatment, had an average ERK level of 10.17 ± 2.98 ng/ml, P1 (50 mg/kg BW). Furthermore, when ethanol extracts were used as opposed to the control group, which received a high-fat diet without treatment, there was an increase in phosphoinositide three-kinase (PI3K) levels (K2). The control group received 9.35 ± 2.87 ng/ml, the treatment group received 100 mg/kg BW (P2) 9.48 ± 1.54 ng/ml, and the treatment group received 150 mg/kg BW (P3) 7.87 ± 1.79 ng/ml. The weight of fat in the abdomen differed between the groups that received a high-fat diet without treatment (K2) and those that received a high-fat diet with treatment (P1, P2, P3; p < 0.05). Conclusion: Anredera cordifolia extract possesses anti-obesity activities by decreasing ERK and increasing PI3K levels, as well as reducing abdominal fat weight. J. Adv. Vet. Anim. Res., 10(4): 809–816, December 2023 http://doi.org/10.5455/javar.2023.j737